Atrial undersensing secondary to quiet timer blanking in pediatric and congenital heart disease patients. Issue 7 (14th June 2017) - von Alvensleben, Johannes C.; Schaffer, Michael; Brateng, Caitlin; Collins, Kathryn K.
Abstract: Background: Atrial undersensing despite normal atrial lead parameters and high amplitude electrograms has been described in adult patients as a consequence of atrial amplifier saturation. Repetitive inputs cause amplifier ringing and undersensing occurs as a consequence of quiet timer blanking. High amplitude ventricular electrograms can also result in atrial blanking secondary to cross‐chamber effect. This has not been described in pediatric patients or epicardial pacing systems and specific risk factors are not known. We describe five cases of atrial undersensing in pediatric and congenital heart disease patients with epicardial dual‐chamber systems and high ventricular lead outputs. Methods: This was a retrospective cohort study of all patients with dual‐chamber pacing systems cared for at the Heart Institute at Children's Hospital Colorado. Results: Five cases of atrial undersensing with normal atrial lead parameters were found. All were epicardial systems with acceptable lead parameters at implantation and Medtronic (Medtronic, Inc., Minneapolis, MN, USA) generators with unipolar leads. Ventricular pacing outputs were elevated at presentation, median 5.5 V (5–7.5). Presenting symptoms were exercise intolerance (four) and detection on routine monitoring (one). Successful interventions included reduction in ventricular lead pacing output (one), programming of rate response (two), and implantation of an alternative generator manufacturer (two). Conclusion: Atrial undersensing secondary to amplifier ringing and quiet timer blanking is an uncommon presentation but may be clinically important in patients with unipolar epicardial atrial leads and high pacing outputs from ventricular leads.